Enhancing cognitive function of healthy Wistar rats with aqueous extract of Centella asiatica - Ayeshah A Rosdah; Evi Lusiana; Muhammad Reagan; Abdurrahman Akib; Fadhila Khairunnisa; Afkara Husna (Acta Biochimica Indonesiana, 2018)
Background: Centella asiatica (L.) Urb is a native herb from Asian countries such as India, China, and Indonesia. This herb has been widely used as a cure for various diseases. However, studies investigating the aqueous extract of Centella asiatica as a nootropic in healthy individuals are still very limited. Objective: This study aims to investigate the potential of aqueous extract of Centella asiatica in enhancing cognitive function of healthy male Wistar rats. Methods: Rats were randomly allocated to four treatment groups, i.e. without treatment and aqueous Centella asiatica extract at doses of 200, 400 and 800 mg/kg. To determine enhancement of cognitive function, novel object recognition (NOR) test was conducted after the course of treatment. Acetylcholine content was assessed by enzyme-linked immunosorbent assay. Results: There was a significantly high preference index towards the novel object in the NOR test in groups treated with 200 mg/kg and 800 mg/kg of the aqueous extract compared to control. This was further confirmed by a significant increase of brain acetylcholine content in rats treated with 200 mg/kg of the extract. Conclusion: Therefore, this study confirms that the aqueous extract is effective in enhancing cognitive performance of healthy Wistar rats.